An investigation into lexical markers of emotion evaluation in political speeches made by the us president barack obama (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
The study aimed to investigate lexical markers of emotion evaluation in political speeches made by US president Barack Obama in terms of syntactic, semantic features in order to help the Vietnamese students of English achieve persuasive and coherent understanding of political language in English concerning emotion. The thesis was designed for the analysis of lexical markers of emotion to help Vietnamese learners of English have better understanding of appraisal in general and emotion in particular. The study focused on lexical markers of emotion in the category of Attitude, one of the three subsystems within the Appraisal theory. This descriptive qualitative study was conducted based on a descriptive framework of Functional grammar by Halliday (1985) and Appraisal theory by Martin (2005). President Obama’s speeches were examined to discover the semantic features his political speeches and to examine the syntactic features in view of clause as message and structural group in functional grammar and in terms of Appraisal theory. The examination of the qualitative information of the lexical markers of emotion in political speeches was done with examples quoted from President Obama's speeches chosen from website www.whitehouse.gov. It was conducted by analysing the data with 200 samples taken from extracts of Obama’s political speeches. The study found that lexical markers of emotion evaluation used in President Obama’s speeches appeared in syntactic forms such as adjective phrases, noun phrases, clauses and sentences to assume the functions of Subject, Predicate, Complement, and Adjunct in the Theme-Rheme structure. Semantically, these lexical markers of emotion evaluation were found to signal the appraisal values of In/Happiness, In/Security, Dis/Satisfaction and Dis/Inclination